Can vessel dimension explain tolerance toward fungal vascular wilt diseases in woody plants? Lessons from Dutch elm disease and esca disease in grapevine - Pouzoulet, Jérôme; Pivovaroff, Alexandria L.; Santiago, Louis S.; Rolshausen, Philippe E. (Frontiers in Plant Science, 2014)
This review illuminates key findings in our understanding of grapevine xylem resistance to fungal vascular wilt diseases. Grapevine (Vitis spp.) vascular diseases such as esca, botryosphaeria dieback, and eutypa dieback, are caused by a set of taxonomically unrelated ascomycete fungi. Fungal colonization of the vascular system leads to a decline of the plant host because of a loss of the xylem function and subsequent decrease in hydraulic conductivity. Fungal vascular pathogens use different colonization strategies to invade and kill their host. Vitis vinifera cultivars display different levels of tolerance towards vascular diseases caused by fungi, but the plant defense mechanisms underlying those observations have not been completely elucidated. In this review, we establish a parallel between two vascular diseases, grapevine esca disease and Dutch elm disease, and argue that the former should be viewed as a vascular wilt disease. Plant genotypes exhibit differences in xylem morphology and resistance to fungal pathogens causing vascular wilt diseases. We provide evidence that the susceptibility of three commercial V. vinifera cultivars to esca disease is correlated to large vessel diameter. Additionally, we explore how xylem morphological traits related to water transport are influenced by abiotic factors, and how these might impact host tolerance of vascular wilt fungi. Finally, we explore the utility of this concept for predicting which V. vinifera cultivars are most vulnerable of fungal vascular wilt diseases and propose new strategies for disease management.